BETWEEN THEORY AND PRACTICE: AN ANALYSIS OF THE GAP IN THEMATIC MODELS IN ELEMENTARY EDUCATION - Norlaili Izzati; Fitria; Agus Mukti Wibowo; Luthfiya Fathi Pusposari (SOSIOEDUKASI, 2026)
This study aims to analyze the gap between the planned and actual implementation of an integrated thematic learning model in science instruction and its implications for students' metacognitive abilities. The study was conducted at MI Mambaul Ulum involving teachers and students participating in integrated thematic science learning. A qualitative descriptive approach was employed, with data collected through classroom observations, interviews, and document analysis. The findings reveal that teachers planned instruction using the Shared Model, which regularly integrates related concepts. However, classroom implementation tends to shift toward the Networked Model, allowing greater flexibility and collaboration. This discrepancy was influenced by time constraints, variations in students' learning abilities, and the demands of differentiated instruction. As a result, students demonstrated limited metacognitive abilities, particularly in regulating and reflecting on their own learning processes. Unlike previous studies that primarily focus on the effectiveness of integrated thematic learning models, this study highlights the discrepancy between instructional planning and classroom implementation and demonstrates its implications for students' metacognitive development. These findings underscore the importance of aligning instructional design with classroom practice and consistently integrating metacognitive strategies to foster students' reflective, critical, and independent thinking.